Declining Fertility in Eritrea Since the Mid-1990s: A Demographic Response to Military Conflict - Woldemicael, Gebremariam (International Journal of Conflict and Violence (IJCV), 2010)
Between the mid-1990s and the early part of the new century, the total fertility rate in Eritrea declined by twenty one percent. Even more striking than the magnitude of this decline within a short period is that it occurred in the absence of any improvements in contraceptive use and without any evident reduction in desired family size. In this study, fertility decline and its underlying factors are examined using data from two waves of the Eritrea Demographic and Health Surveys. The central question is whether the recent decline is an outcome of the 1998-2000 border conflict, is related to changes in women's reproductive intentions, or is due to socio-economic transformations. The findings demonstrate that the fertility decline, especially for first births, is the result less of increased demand for family size limitation and more of the border conflict. Although the conflict seems to have played a role in accelerating the decline in higher-order births, the change seems to be a long-term transition that started before the conflict. These findings imply that military conflicts are unlikely to instigate sustainable fertility decline, but may prompt short-term fertility changes among certain groups or modify an ongoing decline.